2019
DOI: 10.1177/0271121419855692
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Social Stories™ on Challenging Behavior and Prosocial Skills in Young Children: A Systematic Review and Meta-Analysis

Abstract: Social stories are a commonly used intervention practice in early childhood special education. Recent systematic reviews have documented the evidence base for social stories, but findings are mixed. We examined the efficacy of social stories for young children (i.e., 3–5 years) with challenging behavior across 12 single-case studies, which included 30 participants. The What Works Clearinghouse standards for single-case research design were used to evaluate the rigor of studies that included social stories as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Finally, the SS literature has focussed on increasing positive behaviour and reducing negative behaviour (e.g. Wahman et al 2019 ) and this study has highlighted the effective use of SS for supporting adapting to change. The use of SS for teaching new skills (academic/functional) is an under-researched area (Garwood and van Loan 2019 ; Kokina and Kern 2010 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, the SS literature has focussed on increasing positive behaviour and reducing negative behaviour (e.g. Wahman et al 2019 ) and this study has highlighted the effective use of SS for supporting adapting to change. The use of SS for teaching new skills (academic/functional) is an under-researched area (Garwood and van Loan 2019 ; Kokina and Kern 2010 ).…”
Section: Discussionmentioning
confidence: 89%
“…There is less research on the third category of using SS to target managing transitions/novel situations/reducing anxiety, which makes up 9% of the SS literature 1 (Kokina and Kern 2010 ; and no studies in this category were identified by Garwood and van Loan 2019 ). Qi et al’s ( 2018 ) systematic review of SS identified studies that only fell under the categories of increasing positive behaviours/social communication skills and decreasing negative behaviours, and Wahman et al’s ( 2019 ) systematic review only included the categories of increasing positive behaviour and reducing negative behaviour. Whilst the effectiveness of SS is largely evaluated upon research assessing increasing/decreasing behaviour, there is evidence that in practice SS are used for managing transitions/novel situations/anxiety reduction (Briody and McGarry 2005 ; Daly et al 2010 ; Ivey et al 2004 ; Marion et al 2016 ; Morrison and Gullón-Rivera 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…SS have been evaluated for use to improve the performance of typically developing young students displaying problem behaviors (Benish & Bramlett, 2011) and students with autism spectrum disorders (ASDs; Wong et al, 2014), but have not been evaluated with students displaying problematic behaviors who are at risk for disability. Inconsistent conclusions across reviews (Leaf et al, 2015; Wahman, Pustejovsky, Ostrosky, & Santos, 2019; Zimmerman & Ledford, 2017) may be due to procedural differences between studies (i.e., use of multicomponent interventions), differences across participants, and limited or variable study quality. Visual supports have been identified as evidence based for some populations (e.g., students with ASD; Wong et al, 2014) but are widely recommended for use with students with a variety of disabilities (Lawry, Danko, & Strain, 1999; Lequia, Machalicek, & Rispoli, 2012).…”
Section: Social Stories and Visual Supportsmentioning
confidence: 99%
“…Pustejovsky (2018) illustrated the approach in an empirical application. The approach has also been applied in several recent syntheses of SCEDs (e.g., Collins et al, 2020;Froján-Parga, Prado-Gordillo, Álvarez-Iglesias, & Alonso-Vega, 2019;Ledford & Pustejovsky, 2020;Wahman, Pustejovsky, Ostrosky, & Santos, 2019;Zimmerman et al, 2018).…”
mentioning
confidence: 99%